Formulation and Evaluation of Apigenin-Loaded Hybrid Nanoparticles - Imran Kazmi; Fahad A. Al-Abbasi; Syed Sarim Imam; Muhammad Afzal; Muhammad Shahid Nadeem; Hisham N. Altayb; Sultan Alshehri (MDPI AG, 2022)
Apigenin (AGN) is a potent phytochemical with strong antioxidant and anticancer potential. But its therapeutic efficacy is limited due to its high lipophilic characteristics. Therefore, the present investigation aimed to develop AGN-loaded polymer-lipid hybrid nanoparticles (AGN-PLHNPs). Herein, we successfully developed AGN-PLHNPs and optimized them by a 33-Box-Behnken de-sign. The poly (lactic-co-glycolic acid) (PLGA; coded as F1), phospholipon 90 G (PL-90G; coded as F2), and poloxamer 188 (P-188; coded as F3) were considered as the independent factors while particle size (PS; coded as R1), entrapment efficiency (%EE; R2), and cumulative drug release (%CDR; R3) were selected as dependent responses. The average PS, %EE, and %CDR of the AGN-PLHNPs were observed in the range of 101.93 nm to 175.26 nm, 58.35% to 81.14%, and 71.21% to 93.31%, respectively. The optimized AGN-PLHNPs revealed better homogeneity (poly-dispersity index < 0.2) and colloidal stability with high zeta potential (>25 mV). It also exhibited fast release in the initial 4 h after that sustained release up to 48 h of study. Moreover, the results of both DPPH as well as ABTS assays revealed significant improvement in the antioxidant activity. Furthermore, the optimized AGN-PLHNPs exhibited enhanced cytotoxicity efficacy against MCF-7 as well as MDA-MB-231 breast cancer cell lines.